2010
DOI: 10.1158/0008-5472.sabcs10-p1-11-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P1-11-01: ANZAC: A Randomised Neoadjuvant Biomarker Study Investigating the Anti-Tumour Activity of the Addition of Zoledronic Acid to Chemotherapy in Breast Cancer

Abstract: Background: Pre-clinical studies have demonstrated sequence-dependent synergistic anti-tumour effects of chemotherapy (CT) and zoledronic acid (Z) in bone and soft tissue tumours. We have also reported that the addition of Z to neoadjuvant CT appears to improve pathological response in the surgical resection specimen. The ANZAC study aimed to investigate the short-term anti-tumour effects of neoadjuvant CT +/− Z in patients with invasive breast cancer, evaluating biological end-points including apoptosis, prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…To build on the animal data, a neoadjuvant clinical trial in women with breast cancer (ANZAC, NCT00525759) randomised women to a standard chemotherapy regimen of 5-fl uorouracil, epirubicin and docetaxel plus or minus ZA administered as a one time dose the day after the fi rst cycle of chemotherapy. The correlative biomarkers examining apoptosis, proliferation and angiogenesis did not demonstrate frank evidence of an antitumour affect, although a single dose of ZA may not have been suffi cient to cause an appreciable change in the selected biomarkers [83].…”
Section: Translational Questionsmentioning
confidence: 89%
See 1 more Smart Citation
“…To build on the animal data, a neoadjuvant clinical trial in women with breast cancer (ANZAC, NCT00525759) randomised women to a standard chemotherapy regimen of 5-fl uorouracil, epirubicin and docetaxel plus or minus ZA administered as a one time dose the day after the fi rst cycle of chemotherapy. The correlative biomarkers examining apoptosis, proliferation and angiogenesis did not demonstrate frank evidence of an antitumour affect, although a single dose of ZA may not have been suffi cient to cause an appreciable change in the selected biomarkers [83].…”
Section: Translational Questionsmentioning
confidence: 89%
“…Ottewell et al have observed that the administration of doxorubicin 24 h before ZA administration has sustained inhibition of tumour growth and prolonged survival in breast cancer [89]. There are clinical [83]. The neoadjuvant setting of studies like ANZAC provides a unique situation for assessing the impact of ZA on the primary tissue as seen in soft tissue and the ANZAC results highlight the importance of optimising the dose, interval and duration of ZA therapy.…”
Section: Translational Questionsmentioning
confidence: 99%
“…Significant differences in serum vascular endothelial growth factor (VEGF) levels at day 5 and rates of proliferation (Ki-67) at day 21 were seen between the two treatment groups. Further study is required to determine the clinical relevance of these observations [51 ].…”
Section: Prevention Of Metastasis With Bone-targeted Agentsmentioning
confidence: 99%
“…AN-ZAC (Addition of Zoledronic Acid to Pre-operative Chemotherapy, NCT00525759), a randomized phase II feasibility study, aims to look at the short term biological changes in breast tumours following the addition of a single dose of zoledronic acid 24 hours after initial neo-adjuvant chemotherapy is administered to patients with invasive breast cancer [64]. As already described above, preclinical work has highlighted the potential benefit of administering zoledronic acid 24 hours after chemotherapy.…”
Section: Clinical Studies -Does Adding Bisphospho-nates Affect Diseasmentioning
confidence: 99%